1960
DOI: 10.1177/004051756003000506
|View full text |Cite
|
Sign up to set email alerts
|

An Entropy Stress Study of Various Textile Fibers

Abstract: A stress-strain study has been made of various fibers to determine their entropy force behavior at room temperature. The relative importance of the entropy and internal energy forces is shown with some illustrations of the use of these quantities in under standing the fine structure of polymers. Details are presented to show the effects of extension and godet stretch on some samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1961
1961
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…A second region of recoverable strain was attributed to stretching of the helices, and a final region, found above the Tg only, could be attributed to irrecoverable flow. Dart [5] ] had previously found that above the Tg the entropy of PAN fibers decreased with an increase in length; this is consistent with he stretching of a molecular &dquo;spring&dquo; which is initially in its maximum entropy state. The &dquo;spring&dquo; concept will be used extensively in discussion of our data.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…A second region of recoverable strain was attributed to stretching of the helices, and a final region, found above the Tg only, could be attributed to irrecoverable flow. Dart [5] ] had previously found that above the Tg the entropy of PAN fibers decreased with an increase in length; this is consistent with he stretching of a molecular &dquo;spring&dquo; which is initially in its maximum entropy state. The &dquo;spring&dquo; concept will be used extensively in discussion of our data.…”
Section: Introductionsupporting
confidence: 56%
“…Special ' care was needed to produce acceptable fibers at the high and low extremes of the coagulation-temperature range. Normally, at high coagulation temperature ( 70-80 ° C ) macroscopic voids within the fiber become a serious problem [ 5 ] , and filament breakage in the coagulation bath is a problem at low coagulation temperatures. Cross sections of the fibers are shown in Figure 3.…”
Section: Preparation Of Fiber Samplesmentioning
confidence: 99%
“…is given by force-temperature measurements which show that dry rayon has glasslike properties4 and by entropy stress studies that show wet rayon has rubberlike properties. 17 These results indicate that there is a concentration of absorbed water below which the elastic behavior of rayon is essentially glasslike and above which it is essentially rubberlike.…”
Section: Discussionmentioning
confidence: 93%
“…of filament). Iff is the stress in grams per tex and p L the linear density of the filament in tex, then F = 9 8 l f p~ (7) It is convenient to use the specific heat and internal energy per unit mass (cvL and u) rather than the thermal capacity and internal energy of the entire specimen of length L . Now,…”
Section: Range Of Strain Rate For Temperature Changesmentioning
confidence: 99%